STARS AND PARTICLES: WORDS OF THE UNIVERSE - Battiston, Roberto (Annales Kinesiologiae, 2011)
In this paper we review the long history of the relationship of humankind with the universe. From Stonehenge until the modern satellites, our race has always devoted huge resources and the best techniques to decipher messages coming from far away in the cosmos, trying to reach a better understanding of our place in the universe.